ATTITUDES TOWARD WOMEN’S LEADERSHIP: DEVELOPMENT AND VALIDATION OF A NEW SCALE IN THE SAUDI SOCIETY: Actitudes hacia el liderazgo de la mujer: desarrollo y validación de una nueva escala en la sociedad saudita - ALZEIBY, E. A. (Utopía y Praxis Latinoamericana, 2021)
The research sample consisted of (1000) male and female members of the administrative and educational staff and female students at Princess Nourah bint Abdulrahman University (PNU) in Riyadh, Kingdom of Saudi Arabia. The descriptive approach was used. When calculating Pearson’s correlation coefficient, it was found that all Paragraphs correlation values with the total score of the tool are statistically significant and with a high to a very high degree. According to Cronbach’s Alpha reliability, the results confirmed that the study tool has a high degree of reliability in its various dimensions.